ENERGY AND EXERGY ANALYSIS OF SUGARCANE INDUSTRY USING FREE SIMULATOR - Vieira, A. L.; Lima, L. F.; Conceição, W. A. S.; Andrade, C. M. G. (Revista de Engenharia Térmica, 2016)
Due to environmental and economic problems, we need to seek and investigate renewable energy sources. Worldwide, we have a predominant use of energy derived from fossil fuels. In Brazil, much of the energy comes from hydroelectricity. However, it is known that to be dependent predominantly from a main source, could cause logistical problems. A solution to this situation, in Brazil, are sugarcane plants. These plants are normally self-sufficient in terms of energy, but they can still have their energetic and exegetics efficiencies increased. This paper intends to present by simulation (using free software, COCO) that if all machines in the process, steam-powered, were replaced by machines powered by electricity, the yield should increase. We also show that if we replace the turbines by other, working in higher pressures, the energy will have an even greater increase.